A New Quantification Method Using Electrochemical Mass Spectrometry - Xu, Chang; Zheng, Qiuling; Zhao, Pengyi; Paterson, Joseph; Chen, Hao (Journal of the American Society for Mass Spectrometry, 2019)
Mass spectrometry-based quantification method has advanced rapidly. In general, the methods for accurate quantification rely on the use of authentic target compounds or isotope-labeled compounds as standards, which might be not available or difficult to synthesize. To tackle this grand challenge, this paper presents a novel approach, based on electrochemistry (EC) combined with mass spectrometry (MS). In this approach, a target compound is allowed to undergo electrochemical oxidation and then subject to MS analysis. The oxidation current recorded from electrochemistry (EC) measurement provides information about the amount of the oxidized analyte, based on the Faraday’s Law. On the other hand, the oxidation reaction yield can be determined from the analyte MS signal changes upon electrolysis. Therefore, the total amount of analyte can be determined. In combination with liquid chromatography (LC), the method can be applicable to mixture analysis. The striking strength of such a method for quantitation is that neither standard compound nor calibration curve is required. Various analyte molecules such as dopamine, norepinephrine, and rutin as well as peptide glutathione in low quantity were successfully quantified using our method with the quantification error ranging from − 2.6 to + 4.6%. Analyte in a complicated matrix (e.g., uric acid in urine) was also accurately measured. Graphical Abstract